“There aren´t fags here!” Experience of reading and writing at a Center of Confinement in the city of La Plata - Morini, Luciana Daniela (Centro Interdisciplinario de Investigaciones en Género. IdIHCS (CONICET - UNLP). Facultad de Humanidades y Ciencias de la Educación, Universidad Nacional de La Plata, 2021)
The present work analyzes a teaching-learning situation in a literature class in a course that brings together fifth and sixth year students of the Secondary School No. 40 that articulates within the Almafuerte Confinement Center in the city of La Plata, which houses young men in conflict with criminal law. From the analysis of a class register in which Abelardo Castillo's story "The Faggot" was read, multiple questions arise regarding sex-gender categories and historically constructed male and female roles. At the same time, from an ethnographic approach with a gender perspective, we seek to reflect on the institutional space, the corporeality, the use of language, the forms of resistance through parody, the norms of corporal and subjective control and the link between the teacher and the students who are the protagonists of the experience. Finally, it points out the potential of literature to develop debates around these themes.